Pulmonary Rehabilitation for Chronic Obstructive Pulmonary Disease in Natural Disaster Setting - Siti Chandra Widjanantie (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: The frequency of natural disaster in Indonesia has increased recently, while there were still less capacity to overcome the respiratory problem as an impact of disaster. Subjects who havechronic obstructive pulmonary disease (COPD) need to have more attention in dealing with disaster setting.Methods: Literature reviews from the last ten years to find the data of the respiratory-related disease on disaster setting, which need pulmonary rehabilitation.Discussion: Subjects with COPD can get worse aftermath of natural disasters. The number of COPD exacerbation aftermath disaster was increased 1.5 fold. Pulmonary rehabilitation by trained patient forthe self-management of the symptoms was effective to reduce complication, increase the function and social integration.Conclusion: Pulmonary rehabilitation by optimizing community based training for self-management was effective as preparedness for COPD patients in natural disasters.Keywords: Chronic Obstructive Pulmonary Disease (COPD), Community based training, Natural Disaster, Pulmonary Rehabilitation